The Students’ Perceptions Toward Mobile-Based Learning in Learning Writing Skill - Sahib, Nurfaizah; Noni, Nurdin; Muhayyang, Maemuna; Sakkir, Geminastiti (Har Press Indonesia, 2025)
This research explored students' perceptions of the use of mobile-based learning in learning writing skill at an Islamic University. The participants were students from the English Education Department at the Faculty of Tarbiyah, State Islamic University Alauddin Makassar. A descriptive qualitative approach with a case study design was the research design. Data were collected through observations and interviews, and analysed using thematic analysis. The findings indicated that students had positive perceptions toward mobile-based learning, emphasizing its role in enhancing writing skills, offering flexibility and accessibility, promoting autonomous learning, and fostering engagement. Overall, learners expressed positive attitudes toward mobile-based learning, noting that it facilitates the process of learning English writing through the LMS platform and WhatsApp. while also providing access to additional resources related to writing.